2005
DOI: 10.1007/s10802-005-0930-3
|View full text |Cite
|
Sign up to set email alerts
|

Early Adversity and the Prospective Prediction of Depressive and Anxiety Disorders in Adolescents

Abstract: The current study was a prospective exploration of the specificity of early childhood adversities as predictors of anxiety and depressive disorders in adolescents. Participants were 816 adolescents (414 males, 402 females) with diagnostic information collected at age 15; information on early adversities had been collected from the mothers during pregnancy, at birth, age 6 months, and age 5 years for a related study. Adolescents with "pure" anxiety disorders were compared with adolescents with "pure" depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 44 publications
8
94
0
9
Order By: Relevance
“…Studies have shown that adversity experienced in childhood is associated with both depressive and anxiety disorders later in life (Brown & Harris, 1993;Kessler, Davis, & Kendler, 1997). In fact, Phillips, Hammen, Brennan, Najman, and Bor (2005), using the same community sample as the present study, demonstrated that adolescents with a history of pure anxiety disorders were more likely than adolescents with a history of pure depression to have been exposed to various childhood adversities. Other studies have found higher rates of childhood adversity in patients with co-morbid depression and anxiety than in patients with pure depression or pure anxiety (Alnaes & Torgerson, 1990;Mancini et al, 1995), suggesting that childhood adversity may place individuals particularly at risk to experience both anxiety and depression over the course of their lifetime.…”
supporting
confidence: 53%
“…Studies have shown that adversity experienced in childhood is associated with both depressive and anxiety disorders later in life (Brown & Harris, 1993;Kessler, Davis, & Kendler, 1997). In fact, Phillips, Hammen, Brennan, Najman, and Bor (2005), using the same community sample as the present study, demonstrated that adolescents with a history of pure anxiety disorders were more likely than adolescents with a history of pure depression to have been exposed to various childhood adversities. Other studies have found higher rates of childhood adversity in patients with co-morbid depression and anxiety than in patients with pure depression or pure anxiety (Alnaes & Torgerson, 1990;Mancini et al, 1995), suggesting that childhood adversity may place individuals particularly at risk to experience both anxiety and depression over the course of their lifetime.…”
supporting
confidence: 53%
“…2004; Phillips et al. 2005; Read and Hammersley 2005; Cath et al. 2008; Champagne and Curley 2009; Roullet et al.…”
Section: Introductionmentioning
confidence: 99%
“…This study also found significant relationships between depression scores and history of physical and sexual abuse, poor exercise, body mass index (BMI), interpersonal problems with peers, problems with family, and poor school performance [3]. Researchers have also begun to identify a strong link between developmental stressors and an increased risk of depression during adolescence [4][5][6][7]. Moreover, Monroe and Harkness [6], note that an increased emphasis should be placed on the role that life stressors likely play in the association between a premier episode of major affective disorder, and subsequent sensitization to further stressors [6].…”
Section: Introductionmentioning
confidence: 77%
“…In a study examining adversities in adolescence (e.g. parental drinking, parental mental illness, violence in the family home, and parents' marital struggles), researchers found that the experience of adversity was significantly linked to the occurrence of a depressive episode by age 20 [7]. Furthermore, although this research is not specifically focused on rural adolescents, it does lend itself to the importance of depression prevention during this age and stage of development.…”
Section: Introductionmentioning
confidence: 97%